INCREASING STUDENT'S READING COMPREHENSION BY READING COMICS AT THE SEVENTH YEAR OF SMP PGRI KEDAWUNG, SRAGEN IN 2010/2011 ACADEMIC YEAR - INDERIYANI, RINI (2011)
This research is aimed at knowing whether or not teaching reading by reading comics can increase motivation and achievement of Junior High School students'. The result of this study hopefully give contribution in learning English. In this research, teaching reading by reading comics is used to increase students' motivation and their achievement in learning English. This research was carried out at SMP PGRI Kedawung, Sragen, especially in class "VII B" that consists of 42 students. In collecting the required data, the writer did observation, gave test, and analyzed document. There were two cycle in this action research in which pre-test in the early meeting and post-test in the last meeting. She analyzed the data by comparing the result pre-test and post-test. The result of pre-test and post-test are used to know the students' achievement. The mean of the students' achievement after the teacher gave the action 74,5% that belong to good category and the students' mean score before the teacher did the action was 51, 15%. Based on the research finding, it can be concluded that teaching reading by reading comics in teaching English could increase the students' motivation and achievement in reading comprehension. Therefore, it is better for the students to study English carefully through practice and experience, and to be active and creative in learning English. While the teacher should teach the students with comics, process considerable knowledge to manage an interesting classroom, and prepare the lesson they are going to teach as well as possible.